2017
DOI: 10.1177/0145721717713317
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Feasibility Study of a Digital Storytelling Intervention for Immigrant and Refugee Adults With Diabetes

Abstract: Purpose The purpose of this pilot feasibility project was to examine the potential effectiveness of a digital storytelling intervention designed through a community-based participatory research approach for immigrants and refugees with type 2 diabetes mellitus (T2DM). Methods The intervention was a 12-minute culturally and linguistically tailored video consisting of an introduction, 4 stories, and a concluding educational message. A structured interview was used to assess the intervention for acceptability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(93 citation statements)
references
References 53 publications
(61 reference statements)
0
86
0
1
Order By: Relevance
“…Patients either completed written questionnaires [24, 32-36, 38-42, 44-48, 50-52] or were surveyed in-person and by telephone. [37,43,49] Six studies also used biometric data such as blood pressure and hemoglobin A1C readings taken by medical providers. [24, 36-38, 47, 48], and one used a web browser to collect usage statistics about how often patients accessed FPS or didactic content.…”
Section: Data Collectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients either completed written questionnaires [24, 32-36, 38-42, 44-48, 50-52] or were surveyed in-person and by telephone. [37,43,49] Six studies also used biometric data such as blood pressure and hemoglobin A1C readings taken by medical providers. [24, 36-38, 47, 48], and one used a web browser to collect usage statistics about how often patients accessed FPS or didactic content.…”
Section: Data Collectionmentioning
confidence: 99%
“…As shown in Table 2, 10 non-RCT studies, compared to their baseline assessments, reported changes to attitudes, knowledge, behaviors, or clinical outcomes for patients who had been exposed to FPS interventions. Of the 8 non-RCT studies that assessed the impact of FPS on health-related behaviors (e.g., eating more vegetables, using salt substitutes, quitting smoking, or improved foot care) [24,[45][46][47][48][49][50]52], 7 reported positive health behavior change. All four studies that assessed impact on clinical outcomes (e.g., lowering blood pressure or A1C levels) showed improvements compared to baseline.…”
Section: Impact Of Fps In Non-rctsmentioning
confidence: 99%
See 3 more Smart Citations